INOVASI BUDIDAYA IKAN SIDAT PADA MITRA KELOMPOK PT. PERMANA SIDAT INDONESIA DENGAN MENGGUNAKAN BISNIS MODEL CANVAS (BMC) - Muhammad Fatihkul Umam; Moh, Agung Surianto (Pusat Riset dan Inovasi Nasional, 2021)
Abstract The fishing industry in Indonesia faces various problems, so in order to ensure that its business continues, the Lamongan Eel Cultivator Group must be able to make various improvements and innovations in improving its performance. The purpose of this research is not only as a form of community service but also to help fish cultivators formulate a new business model. Research data is primary data obtained directly from the results of interviews and Focus Group Discussions with members of the fish farming group. The analytical tools used are SWOT Analysis and Canvas Business Model with 9 elements. This research is focused on creating a new business model with the Business Model Canvas (BMC) approach which sees the company through nine elements, namely: (1) Customer segmentations, (2) Value Propositions, (3) Channels, (4) Customer relationships, (5 ) Revenue streams, (6) Key Resources, (7) Key Activities, (8) Key Partnerships, and (9) Cost Structure. The results of this study indicate that the business model that has been carried out by the Fish Farming Group (POKDAKAN) found weaknesses in the 9 elements of BMC, therefore it is necessary to make improvements to all elements.